The Contribution of Drug Overdose to Educational Gradients in Life Expectancy in the United States, 1992–2011 - Ho, Jessica Y. (Demography, 2017)
Over the past two decades, the United States has witnessed a dramatic rise in drug overdose mortality. Educational gradients in life expectancy widened over the same period, and it is likely that drug overdose plays a role in this widening, particularly for non-Hispanic whites. The contemporary drug epidemic is distinctive in terms of its scope, the nature of the substances involved, and its geographic patterning, which influence how it impacts different education groups. I use data from vital statistics and from the National Health Interview Survey to examine the contribution of drug overdose to educational gradients in life expectancy from 1992–2011. I find that over this period, years of life lost due to drug overdose increased for all education groups and for both males and females. The contribution of drug overdose to educational gradients in life expectancy has increased over time and is greater for non-Hispanic whites than for the population as a whole. Drug overdose accounts for a sizeable proportion of the increases in educational gradients in life expectancy, particularly at the prime adult ages (ages 30–60) where it accounts for 25–100% of the widening in educational gradients between 1992–2011. Over time, drug overdose mortality has increased more rapidly for females than for males, leading to a gender convergence. These findings shed light on the processes driving recent changes in educational gradients in life expectancy and suggest that effective measures to address the drug overdose epidemic should take into account its differential burden across education groups.